Study on Implementation of Impact Fishermen’s Income Enhancement Economy Public Village Boneog Districts Banawa Donggala District - Alatas, Umar; Umar A, Muhammad (International Journal of Social Sciences and Management, 2022)
The purpose of this study was to determine the effect of fishermen's income on improving the economy of the community in Boneoge village, Banawa district, Donggala Regency. The sample used in this study were fishermen in Boneoge Village, Banawa District, Donggala Regency, and set as many as 50 people by snowball sampling. This type of quantitative descriptive research uses a simple regression analysis method. The results showed that the adjusted R2 value was 0.757, this means that 76% of the variation in the increase in the economic activity of fishermen's households can be explained by variations in the independent variable, namely fishermen's income. While the remaining 29% is explained by other factors outside the model. The conclusion of this research is. from the regression coefficient value of fishermen's income and the level of significance, that fisherman's income has a positive and significant effect on increasing the economic activities of fishing communities in Boneoge Village, Banawa District, Donggala Regency. This is because the fishermen's income is quite high from fishing so that it encourages per capita growth of the community which supports an increase in the economy of Boneoge Village, Banawa District, Donggala Regency. Int. J. Soc. Sc. Manage. Vol. 9, Issue-3: 113-119.